ANALYSIS OF DENOTATIVE AND CONNOTATIVE MEANINGS ON SONG LYRICS BY IWAN FALS - Yogi Purnama; Royan Nur Fahmi (Universitas Indraprasta PGRI, 2020)
This study aims to describe the meaning of denotation, connotations, in the lyrics of Iwan Fals songs. The method used in this research is to use a qualitative descriptive approach to reveal the meaning of denomination and connotation. Data collection techniques are carried out using the analysis of sentence expressions. This study resulted in the conclusion that the use of denotative meaning by 68.75%, the use of positive connotative meaning by 21.09%, the use of negative connotative meaning by 11.32%.